2011
DOI: 10.2147/opth.s16727
|View full text |Cite
|
Sign up to set email alerts
|

High Dk piggyback contact lens system for contact lens-intolerant keratoconus patients

Abstract: Background:The aim of the study was to examine the clinical success of high Dk (oxygen permeability) piggyback contact lens (PBCL) systems for the correction of contact lens intolerant keratoconus patients.Methods:Sixteen patients (29 eyes) who were not able to wear gas-permeable rigid lenses were included in this study. Hyper Dk silicone hydrogel (oxygen transmissibility or Dk/t = 150 units) and fluorosilicone methacrylate copolymer (Dk/t = 100 units) lenses were chosen as the PBCL systems. The clinical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Finally, combination systems have lower oxygen permeability compared with single lens systems. This last drawback has been reduced over time as newer high-DK hydrogel and gas permeable materials have become available for use in PB systems 9 . The disadvantages of PB systems are offset by the increased comfort of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, combination systems have lower oxygen permeability compared with single lens systems. This last drawback has been reduced over time as newer high-DK hydrogel and gas permeable materials have become available for use in PB systems 9 . The disadvantages of PB systems are offset by the increased comfort of the system.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,5 , The use of PB systems have been reported in patients with other causes of irregular astigmatism, including penetrating corneal trauma. 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…PBCL is indicated in patients with RGP discomfort or intolerance, unstable RGP on the eye, popping out of lens, 3 and 9 O’ clock staining with RGP fit and presence of scar. [1920] A PBCL system is also indicated in some patients to improve comfort.…”
Section: Soft Spherical/soft Toric Lensesmentioning
confidence: 99%
“…Contact lenses have some advantages over spectacle corrections (3,4). There are several options such as rigid gas-permeable (RGP) contact lenses (5), hybrid contact lenses (6), piggyback lenses (7) and scleral contact lenses (8).…”
Section: Introductionmentioning
confidence: 99%
“…There are several options such as rigid gas-permeable (RGP) contact lenses (5), hybrid contact lenses (6), piggyback lenses (7) and scleral contact lenses (8). RGP lenses are traditionally first choice because of their success in improving visual acuity (9) RPG lenses improve visual acuity by their refractive power and also by flattening the anterior cornea, increasing the thinnest corneal thickness, and reducing anterior surface high-order aberrations (3,4). Previous studies showed that RGP contact lenses provide a significant improvement in visual acuity compared to spectacles-corrected visual acuity in patients with high corneal astigmatism (10), and keratoconus (11).…”
Section: Introductionmentioning
confidence: 99%